Вплив таутомеризації нуклеотидних основ на конформаційні властивості нуклеозидів: квантово-механічне дослідження методом функціонала густини - Кочіна, О.С.; Жураківський, Р.О.; Говорун, Д.М. (Видавничий дім "Академперіодика" НАН України, 2008)
Firstly, the influence of DNA nucleobase tautomeric status change on conformational and energetic properties of canonical nucleosides 2′-deoxyadenosine (dAdo), 2′-deoxyguanosine (dGuo), 2′-deoxycytidine (dCyd), and 2′-deoxythymidyne (dThd) is studied by the quantummechanical DFT method with B3LYP/6–31G(d, p) basis set. It is determined that tautomeric transitions in purine nucleosides are almost influenceless on a sugar residue conformation and
its orientation against nucleobase. On the other hand, this effect is strong enough in pyrimidine nucleosides, and its trend is clearly defined.